Dysregulation of autophagosome–mitochondria contacts contributes to autophagy dysfunction and neurodegeneration in tauopathy - Nuo Jia; Hongyuan Guan; Yantao Zuo; Yu Young Jeong; Niharika Amireddy; Gavesh Rajapaksha; Cuauhtemoc Ulises Gonzalez; Nora Jaber; Yun-Kyung Lee; Marialaina Nissenbaum; David J. Margolis; Wei Dai; et al. (Proceedings of the National Academy of Sciences, 2026)
Mitochondria (Mito) engage in extensive communication with other organelles through membrane contacts. Perturbed mitochondria–organelle interactions are indicated in a variety of neurodegenerative diseases, but the underlying mechanisms remain poorly understood. Here, we report a class of mitochondria–organelle communication: autophagosome/autophagic vacuole (AV)–Mito contact, which exhibits hypertethering in tauopathy neurons, consequently hampering AV retrograde transport. Such defects are attributed to accelerated turnover of the contact release factor TBC1D15, triggered by mitochondrial bioenergetic deficit-induced hyperactivity of the adenosine monophosphate-activated protein kinase (AMPK). Increasing TBC1D15 levels or repressing AMPK activity normalizes AV-Mito contact release and restores retrograde transport of AVs, thereby increasing autophagic cargo clearance and reducing tau burden in tauopathy axons. Furthermore, overexpression of TBC1D15 enhances autophagic clearance and attenuates tau pathology, alleviating neurodegeneration and cognitive dysfunction in tauopathy mice. Taken together, our study provides mechanistic insights into AV-Mito contact dysregulation in tauopathy-related autophagy failure, laying the groundwork for the development of potential therapeutics to combat tauopathy diseases.